POLARIZATION AND INTERVENTION-BASED P/CVE PROGRAMS IN CANADA - Sara K. Thompson (The Journal of Intelligence, Conflict and Warfare, 2024)
On November 13th, 2023, Dr. Sara K. Thompson presented Polarization and Intervention-based P/CVE Programs in Canada for this year’s West Coast Security Conference. The key points discussed were the typology of extremist violence, the processes of radicalization and mobilization to violence, the threat landscape in Canada, past and present (and the impact of social polarization), and the somewhat recent incorporation of prevention/intervention programming into the broader national security apparatus.